(untitled) (International conference on multidisciplinary science, 2025)
Childhood injuries are a serious global issue and one of the leading causes of mortality and disability among children. This scientific article examines and evaluates domestic injuries among school-age children based on the example of the Khorezm region and discusses the obtained data.